SURGICAL TREATMENT OF WOUNDS OF THE NECK IN PRACTICE OF THE EMERGENCY HOSPITAL DURING PEACETIME - V. B. Mosyagin; V. F. Rylkov; A. A. Moiseev (Вестник хирургии имени И.И. Грекова)
The data of the follow-up study of 60 patients with wounds of the neck are presented in this article. The authors describe the volume and severity of injuries of the neck and at the same time examine the difficulties of diagnostics and treatment. The scope of investigations, the necessity of consultation of «narrow» specialist, the volume of surgical handbook and the conservative therapy are determined. The significance of the up-to-date methods of instrumental researches, such as computed tomography, Doppler tomography, are emphasized particularly for evaluation of the injury volume.